Teacher`s Challenges and Efforts in Teaching English Vocabulary for Deaf Students: A Case Study of Non-Certified Special Education English Teacher at SMALB-B Dharma Asih Pontianak - Egy Prasetya; Rahayu Apriliaswati; Luwandi Suhartono; Endang Susilawati; Dwi Riyanti (Kirana Publisher (KNPub), 2023)
The present study was conducted in order to find out the challenges faced by non-certified special education English teacher in teaching English vocabulary for deaf students and the teacher`s efforts to face those challenges. This was a case study design which used qualitative method as the methodology. The data were taken from the interview and observations of the non-certified special education English teacher who taught English at the X grade of SMALB-B Dharma Asih Pontianak. The result of the study showed that there were several challenges such as students` misinterpretation of words from teacher`s similar lip movements, students` less attention, delivering the meaning of the words, students` lack of articulation, comprehension, and remembering English vocabulary, little experiences of the teacher in using sign language, and the needs of repetition. There were also several efforts to face those challenges such as providing different English vocabulary in each meeting, using picture as a media, using sign language as an alternative communication, drilling, and waving either patting on deaf students` shoulder to get their attention.